Some Aspects of Supersymmetric Field Theories with Minimal Length and Maximal Momentum - Kourosh Nozari; F. Moafi; F. Rezaee Balef (Advances in High Energy Physics)
We consider a real scalar field and a Majorana fermion field to construct a supersymmetric quantum theory of free fermion fields based on the deformed Heisenberg algebra